Penerapan Pembelajaran Berbasis Proyek Menggunakan Metode Blended Learning untuk Meningkatkan Hasil Belajar Mahasiswa - Sutrisno, Sutrisno; Lestari, Intan; -, Rahmi - (Experiment: Journal of Science Education, 2024)
The aim of this research is to improve student learning outcomes in chromatographic analysis courses by implementing a project-based learning model using a blended learning method, namely face-to-face and online via the Learning Management System (LMS) platform. Chromatographic analysis is known as a subject that is theoretically easy to understand, but in the analysis of chemical reactions that occur in the separation process it is still difficult for students to describe so that appropriate visualization technology needs help in describing the process of chemical reactions occurring when the separation takes place. Material using the project-based learning model in the LMS was developed using the Research and Development (RD) 4-D Model (four D model) method. Next, a formative evaluation is carried out for the testing stage of the teaching material. The application of this learning shows that students experience increased understanding in analyzing material and can complete projects that are presented well in class. The advantage of implementing the blended learning method is that students can access the material repeatedly and can confirm during face-to-face lectures in class. The application of the project-based learning model is able to direct students to be more active in solving direct problems, compiling them in the form of reports and presenting the results they have obtained. In this way, students learn to be more responsible in completing projects given by the lecturer and student learning outcomes increase.